APLIKASI ANDROID SISTEM PAKAR UNTUK MENDIAGNOSA PENYAKIT CAMPAK PADA ANAK - Harun, Muhamad (Aksara Public, 2018)
In childhood, physical growth begins to increase both height and weight along with the development of muscle coordination and mental abilities. In that phase, all children would have experienced sick in his life, which mostly caused by pathogenic microorganisms such as bacteria, viruses, parasites and fungi. Early detection and treatment of the disease Measles must be done quickly and accurately, because measles can be easily cured but deadly if left untreated. The disease is most common in children, and especially in developing countries such as Africa and some Southeast Asia. Measles can cause children vulnerable to diarrhea, pneumonia, blindness and brain damage. So in need The Expert System for Diagnosing Measles in children a more practical and efficient to the android based mobile devices by utilizing the development of IT technology and knowledge of modern medical world. This expert system using techniques Best First Search and Forward Chaining with a knowledge base derived from a variety of sources related to measles to get the final result of the conclusions and recommendation of treatment.